Transformation and scattering activities of the receptor tyrosine kinase RON/Stk in rodent fibroblasts and lack of regulation by the jaagsiekte sheep retrovirus receptor, Hyal2 - Miller A Dusty; Van Hoeven Neal S; Liu Shan-Lu (BMC Cancer, 2004)
Abstract Background The envelope (Env) protein of jaagsiekte sheep retrovirus (JSRV) can transform cells in culture and is likely to be the main factor responsible for lung cancer induction by JSRV in animals. A recent report indicates that the epithelial-cell transforming activity of JSRV Env depends on activation of the cell-surface receptor tyrosine kinase Mst1r (called RON for the human and Stk for the rodent orthologs). In the immortalized line of human epithelial cells used (BEAS-2B cells), the virus receptor Hyal2 was found to bind to and suppress the activity of RON. When Env was expressed it bound to Hyal2 causing its degradation, release of RON activity from Hyal2 suppression, and activation of pathways resulting in cell transformation. Methods Due to difficulty with reproducibility of the transformation assay in BEAS-2B cells, we have used more tractable rodent fibroblast models to further study Hyal2 modulation of RON/Stk transforming activity and potential effects of Hyal2 on RON/Stk activation by its natural ligand, macrophage stimulating protein (MSP). Results We did not detect transformation of NIH 3T3 cells by plasmids expressing RON or Stk, but did detect transformation of 208F rat fibroblasts by these plasmids at a very low rate. We were able to isolate 208F cell clones that expressed RON or Stk and that showed changes in morphology indicative of transformation. The parental 208F cells did not respond to MSP but 208F cells expressing RON or Stk showed obvious increases in scattering/transformation in response to MSP. Human Hyal2 had no effect on the basal or MSP-induced phenotypes of RON-expressing 208F cells, and human, mouse or rat Hyal2 had no effect on the basal or MSP-induced phenotypes of Stk-expressing 208F cells. Conclusions We have shown that RON or Stk expression in 208F rat fibroblasts results in a transformed phenotype that is enhanced by addition of the natural ligand for these proteins, MSP. Hyal2 does not directly modulate the basal or MSP-induced RON/Stk activity, although it is possible that adaptor proteins might mediate such signaling in other cell types.